The Impact of Status-Free Relationships on the Academic Achievement of 12th Grade Students at Atisa Dipamkara High School in the 2025/2026 Academic Year - Georgius Rocki Agasi; Suta Viriya Ferdinand Oey; Fifiana Padma Kusuma; Keshia Hewit Maranatha; Kaynard Jevera (Eduvest - Journal of Universal Studies, 2026)
A relatively new phenomenon known as Hubungan Tanpa Status (HTS), or situationship, refers to a relationship between two individuals who behave like a romantic couple but without clarity of status or commitment. This research was conducted to examine the influence of Hubungan Tanpa Status (HTS) on the psychological and academic aspects of 12th grade students at Atisa Dipamkara High School for the 2025/2026 Academic Year, with a focus on their subjective experiences regarding the level of ambiguity and emotional uncertainty within HTS relationships. This study employs a qualitative approach with a phenomenological method design. The subjects of this study consisted of 15 Grade XII students of Atisa Dipamkara High School for the 2025/2026 Academic Year, selected using purposive sampling, conducted from October 13 to November 10, 2025. The results showed that the relationship between HTS status and academic achievement had a moderate positive correlation, whereby the presence of HTS increased motivation such that academic achievement tended to improve. The study also explored participants' interpretations of the experiences and lessons obtained from HTS relationships. Some participants defined HTS as "a relationship without status — like a friend, but too close." This research may serve as a reference for parents, teachers, and students alike in understanding the psychological conditions that arise during adolescent development.